Masculinity and Suicidal Desire in a Community Sample of Homeless Men: Bringing Together Masculinity and the Interpersonal Theory of Suicide. Issue 3 (October 2019) - Genuchi, Matthew C.
Men's high suicide death rates are likely associated with a range of factors, notably men's conformity to predominant masculine gender role norms and men's gender-related attitudes toward suicide death based on those norms. The purpose of this study was to investigate how two models integrating men's conformity to hegemonic masculine gender role norms, perceived burdensomeness, and thwarted belongingness predict the existence and severity of suicidal ideation in a sample of men at high risk for suicide, homeless men. The study results indicated that multiple norms were predictive of the existence or severity of suicidal ideation while perceived burdensomeness predicted both suicide ideation and the severity of ideation.